Influence of Social Media Emotional Word of Mouth on Institutional Investors’ Decisions and Firm Value - Nguyen, Hang; Calantone, Roger; Krishnan, Ranjani (Management Science, 2020)
This paper examines how customer sentiment expressed through social media influences institutional investors’ investment decisions and firm value. We use psychology theory to classify the emotional content of social media-based word of mouth, which we refer to as ESWOM. We examine whether ESWOM influences institutional investors’ stockholdings differentially based on investor type and if institutional investors’ stockholdings mediate the relation between ESWOM and firm value. We identify eight types of ESWOM by linguistically interpreting web scrapings of millions of social media posts on 38 corporate brands for the 2007–2015 period. We find differential effects of ESWOM on stockholdings of institutional investors. Dedicated and quasi-index institutional investors increase their stockholdings in response to increases in positive ESWOM such as joy and trust. Transient investors decrease their stockholdings in response to increases in negative ESWOM such as anger, disgust, and fear. Competitive intensity and intangible asset intensity influence these results. Path analysis indicates that ESWOM influences firm abnormal stock returns and idiosyncratic risk both directly and indirectly through its effects on institutional investors’ stockholdings. These findings support our hypothesis that investors’ responses to customer sentiment vary based on whether they follow long-term or short-term investment strategies. Our research highlights the importance of understanding the heterogeneous preferences of institutional investors and their use of social media information for decision making. This paper was accepted by Suraj Srinivasan, accounting.